2010
DOI: 10.1119/1.3318805
|View full text |Cite
|
Sign up to set email alerts
|

Do advanced physics students learn from their mistakes without explicit intervention?

Abstract: We discuss a case study in which 14 advanced undergraduate physics students taking an honor-level quantum mechanics course were given the same four problems on midterm and final exams. The solutions to the midterm problems were provided to students. Their performance on the final exam shows that although some advanced students performed equally well or improved compared to their performance on the midterm exam on the problems given twice, a comparable number performed less well on the final than on the midterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 36 publications
2
66
0
Order By: Relevance
“…Since experts learn from their own mistakes, they are unlikely to make the same mistakes when asked to solve a problem a second time, especially if they have had access to a correct solution. Unfortunately, for many students in physics courses, problem solving is a missed learning opportunity [10][11][12][13][14][15][16][17][18]. Without guidance, students often do not reflect upon the problem solving process after solving problems in order to learn from them nor do they make an effort to learn from their mistakes after the graded problems are returned to them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since experts learn from their own mistakes, they are unlikely to make the same mistakes when asked to solve a problem a second time, especially if they have had access to a correct solution. Unfortunately, for many students in physics courses, problem solving is a missed learning opportunity [10][11][12][13][14][15][16][17][18]. Without guidance, students often do not reflect upon the problem solving process after solving problems in order to learn from them nor do they make an effort to learn from their mistakes after the graded problems are returned to them.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Mason and Singh [18] investigated the extent to which upper-level students in quantum mechanics learn from their mistakes. They administered four problems in the same semester twice, on both the midterm and final exams in an upper-level quantum mechanics course.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several prior studies have found that many advanced students struggle with the foundational issues in quantum mechanics including measurement (e.g., see [1][2][3][4][5][6][7][8][9][10][11][12]). Studies have focused on diverse pedagogical approaches for helping students learn quantum mechanics better (e.g., see [13][14][15][16][17][18][19][20][21][22][23][24][25][26]), and visualization tools such as QuVIS and QuTIP have been developed to help students develop intuition about quantum mechanical phenomena [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The study of student understanding of advanced topics is becoming increasingly prevalent in physics education research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Investigating upper-division undergraduate students provides a snapshot of the intellectual journey from novice introductory student to expert physicist that may reveal key components of this transition [19].…”
Section: Introductionmentioning
confidence: 99%